2019
DOI: 10.1016/j.pedn.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The Practice of Mutual Protection in the Care of Children with Palliative Care Needs: A Multiple Qualitative Case Study Approach from Jordan

Abstract: This study explores the experience of disclosing critical information in the care of children with palliative care needs, from the perspective of physicians, nurses, and mothers in Jordan. Design and Methods: This study employed a qualitative case study approach. It was conducted in three paediatric units in a Jordanian hospital. Each case comprised a child aged 1-12 years with a condition eligible for palliative care who received health care in one of these units, and their most involved carers (e.g. mother, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…A study conducted by (Atout, 2017) to understand the experience of communication with children with palliative care needs from the perspectives of Jordanian parents and health professionals found that the protective approach demonstrated by children might originate from the protective environment in which children live (Atout, 2017). The current findings substantiate previous qualitative studies (Atout et al, 2019;Van der Geest et al, 2015) that show that children at a certain developmental age and experience are aware of the expected prognosis of death, but they hide this from their parents as a result of their knowledge of how painful this topic is to their parents.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A study conducted by (Atout, 2017) to understand the experience of communication with children with palliative care needs from the perspectives of Jordanian parents and health professionals found that the protective approach demonstrated by children might originate from the protective environment in which children live (Atout, 2017). The current findings substantiate previous qualitative studies (Atout et al, 2019;Van der Geest et al, 2015) that show that children at a certain developmental age and experience are aware of the expected prognosis of death, but they hide this from their parents as a result of their knowledge of how painful this topic is to their parents.…”
Section: Discussionsupporting
confidence: 89%
“…Cultural background is one of the most significant issues that can affect the degree of openness in communication between children and parents. A study of Jordanian mothers found that they tend to avoid sensitive areas such as delivering bad news, talking about prognosis or death with their children with palliative care needs, especially if they perceived their children did not want to discuss such matters with them (Atout, 2017;Atout et al, 2019). Cultural differences are also seen in healthcare professionals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By setting these boundaries, nurses can protect the privacy of patients who are at risk of causing conflict in the therapeutic relationship, especially patients with trauma (De Clercq et al, 2020;Unhjem, Vatne, et al, 2018). According to nurses, this boundary also protects integrity and personal authority of nurses as nurses set professional boundaries to avoid emotional dangers that may arise as a reaction when a patient dies (Atout et al, 2019;Martínez-Morato et al, 2021b;Smythe et al, 2018b;Unhjem, Vatne, et al, 2018;Zugai et al, 2018). Nurses try to stay within professional boundaries when they care for patients to protect themselves from situations that trigger emotional responses.…”
Section: Aims and Benefits Of Professional Boundariesmentioning
confidence: 99%
“…One of the things that is common in professional boundaries is related to excessive involvement, both related to relationships, emotional aspects, and privacy (Fronek & Kendall, 2016). Nurses who become emotionally close to the patient or perceive the patient as someone special and act according to personal closeness are signs of overinvolvement in the nurse-patient relationship (Atout et al, 2019;College of Registered Nurses of Manitoba, 2019;Sanders et al, 2012).…”
Section: Types Of Professional Boundariesmentioning
confidence: 99%
“…35 of 2014 concerning amendments to Law No. 23 of 2002 concerning Child Protection, which substantively regulates several issues including children in conflict with the law, children from minority groups, children victims of economic and sexual exploitation, trafficked children, children affected by riots, children refugees, and children in armed conflict situations, child protection based on principles of non-discrimination, the best interests of the child, respect for the views of the child, the right to life, growth, and development (Atout et al, 2019;Ferguson & Norton, 2011;Grace et al, 2019;Munro, 2019). In its implementation, this law has been in line with the mandate of the 1945 Constitution regarding the guarantee of human rights, that children as human beings have the same rights to grow and develop.…”
Section: Introductionmentioning
confidence: 99%